Design principles to facilitate e-learning And their application to promote social value creation in residential development - Ivarsson, Denice (My University, 2026)
This thesis establishes an evidence-based framework of design principles to optimize asynchronous e-learning. The framework was applied to a digital course raising awareness of social value creation within residential development. A systematic literature review was conducted and supplemented by multimedia learning theories. A manual thematic analysis of this literature resulted in a comprehensive framework of 36 design principles organized into five themes: Navigation, Content Structure, Content Representation, Exercises, and Feedback. Two qualitative interviews were conducted with residential developers to calibrate the illustrations of the course to industry-specific expectations. The empirical results revealed a strong participant preference for watercolor illustration style and photorealism over low- detailed silhouettes. Choosing watercolor illustrations represents a critical compromise between established multimedia learning theory that advocates schematic visuals, emotional design that highlights the importance of color and the professionals’ expectations of high-quality visualizations. The synthesized framework and visual strategies were implemented to develop a prototype e-learning course. Evaluation from the client validated the course’s instructional clarity, intuitive navigation, and psychological alignment with neuroarchitecture concepts. However, the implementation process exposed technical limitations imposed by developing within Microsoft PowerPoint, which lacks the capacity for assessment data collection and solutions for high-engagement interactivity. Consequently, this study concludes that while slide-based platforms can deliver functional e-learning, future development might require migrating to a dedicated Learning Management System (LMS). The integration of audio narration would support learning further utilizing both visual and auditory channels. This thesis aims to bridge the gap between cognitive multimedia theory and industry-specific cultures, providing a foundation for future empirical research into the boundary conditions of emotional design in professional education.